Dampak Psikologis Pengalaman Kerentanan yang Dialami Perempuan Purna Pekerja Migran Indonesia: Studi Kasus pada Kantong Buruh Migran di Kota Makassar - Nur Ismi Ramadani (Yinyang: Jurnal Studi Islam, Gender dan Anak, 2021)
This study aims to describe the psychological Impact of vulnerability experiences experienced by retired Indonesian migrant workers who experience vulnerability from unpleasant treatment during the migration process. This research is a case study with a descriptive qualitative research approach and uses data collection methods, namely in-depth interviews and observations. The subjects of this studu were three women who live in Bangkala Village, Manggala District, Makassar city, who have backgrounds as former women migrant workers. The results of the data analysis show that the subject experiences various psychological dynamic conditions that greatly impact the vulnerability experienced during his tenure as migrant workers in the oil palm plantation sector. Such as trauma, emotional disturbances and anxiety disorder with different psychological coping strategies depending on the specific situation experienced by each subject.